Antimicrobial Activity and Mode of Action of N-Heterocyclic Carbene Silver(I) Complexes - Giusy Castagliuolo; Michela Di Napoli; Tshering Zangmo; Joanna Szpunar; Luisa Ronga; Anna Zanfardino; Mario Varcamonti; Diego Tesauro (Molecules)
Silver drugs have played a vital role in human healthcare for the treatment of infections for many centuries. Currently, due to antibiotic resistance, a potential scenario or the application of silver complexes may arise as substitutes for conventional antibiotics. In this perspective, N-heterocyclic carbene (NHC) ligands have been selected as carrier molecules for silver ions. In this study, we selected two mono NHC-silver halide complexes: bromo[1,3-diethyl-4,5-bis(4-methoxyphenyl)imidazol-2-ylidene]silver(I) (Ag4MC) and chloro[2-pyridin- N-(2-ethylacetylamido)-2-yl-2H-imidazol-2-ylidene]silver(I) (Ag5MC), and two cationic bis NHC silver complexes: bis[1,3-diethyl-4,5-bis(4-methoxyphenyl)imidazol-2-ylidene]silver(I) (Ag4BC) and bis[2-pyridin-N-(2-ethylacetylamido)-2-yl-2H-imidazol-2-ylidene]silver(I) (Ag5BC). The inhibitory properties of the four complexes were evaluated for their antimicrobial potential against a set of Gram (+) and Gram (−) bacterial strains and the fungus C. albicans. In addition, further investigations were made using fluorescence and scanning electron microscopy (SEM) in order to gain more insights into the mechanism of action. Some preliminary information on the Ag target was obtained by analyzing the cytosol of E. coli treated with Ag5MC by size-exclusion chromatography (SEC) coupled with inductively coupled plasma mass spectrometry (ICP-MS).